Human resources strategy in hospital industry development with the mediating role of competitive advantage - Aqheli Moghanjooghi , Vali; Rahmani Yoshanloui, Kamaladdin (Social Determinants of Health, 2021)
Introduction: Today's organizations are looking for factors that create a competitive advantage. Human resources are one of the best factors in creating a competitive advantage. Human resource strategies focus on the organization's goals, what needs to be done, and what needs to be changed. Therefore, the realization of growth and development strategies depends on the desirability of human resource strategies. The present study aimed at investigating the effect of human resource strategies in hospital industry development considering the mediating role of competitive advantage. Methods: The study is applied in terms of purpose and descriptive-correlational in terms of data collection. The statistical population included private and public agencies and organizations related to hospital industry and hospital industrial development. Using Cochran's formula, 265 people were determined as a statistical sample and a simple random sampling method was used to distribute the research questionnaires. To collect data, three questionnaires, including human resources strategy questionnaire, hospital industry development questionnaire, and competitive advantage questionnaire were used. To analyze data, the structural equation technique in the form of SMART PLS software was used. Results: The results revealed that the competitive advantage mediated the relationship between human resource strategy and hospital industry development. In fact, the direct impact of human resource strategies on industrial development was 0.343 and indirect impact of human resource strategies on industrial development mediated competitive advantage was 0.228. Conclusion: The research results suggest that human resource strategies should create competitive advantages to move towards hospital industry development based on existing potentials in the province.